Asteroseismology of 1523 misclassified red giants using Kepler data. Issue 2 (19th August 2016) - Yu, Jie; Huber, Daniel; Bedding, Timothy R.; Stello, Dennis; Murphy, Simon J.; Xiang, Maosheng; Bi, Shaolan; Li, Tanda
Abstract: We analysed solar-like oscillations in 1523 Kepler red giants which have previously been misclassified as subgiants, with predicted νmax values [based on the Kepler Input Catalogue (KIC)] between 280 and 700  μHz. We report the discovery of 626 new oscillating red giants in our sample, in addition to 897 oscillators that were previously characterized by Hekker et al. from one quarter of Kepler data. Our sample increases the known number of oscillating low-luminosity red giants by 26 per cent (up to ∼1900 stars). About three quarters of our sample are classified as ascending red giant branch stars, while the remainder are red-clump stars. A novel scheme was applied to determine Δν for 108 stars with νmax close to the Nyquist frequency (387 μHz > νmax > 387 μHz). Additionally, we identified 47 stars oscillating in the super-Nyquist frequency regime, up to 387 μHz, using long-cadence light curves. We show that the misclassifications are most likely due to large uncertainties in KIC surface gravities, and do not result from the absence of broad-band colours or from different physical properties such as reddening, spatial distribution, mass or metallicity. The sample will be valuable to study oscillations in low-luminosity red giants and to characterize planet candidates around those stars.